2010
DOI: 10.3986/ac.v39i2.101
|View full text |Cite
|
Sign up to set email alerts
|

Tracer tests as a tool for planning the monitoring of negative impacts of the Mozelj landfill (SE Slovenia) on karst waters

Abstract: IzvlečekUDK 504.054:556.34.04(497.4) Janja Kogovšek & Metka Petrič: Sledilni poskusi kot orodje za načrtovanje monitoringa negativnih vplivov odlagališča odpadkov Mozelj (JV Slovenija) na kraške vode Sledilni poskusi so ena izmed najbolj uporabni� raziskovalni� metod v kraški �idrogeologiji, pokazali pa so se kot zelo primerni tudi pri reševanju različni� aplikativni� problemov. V zadnji� leti� smo tako izvedli serijo sledilni� poskusov, ki so služili kot strokovna podlaga za izdelavo programa monitoringa kako… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…A short flow distance or travel time between drilling impact and sampling point is a likely prerequisite. However, in the setting of the construction project, tracers typically used in karsts appear to be unfeasible (Goldscheider et al 2008) and other methods approved in boreholes are unpromising (Kogovšek & Petrič 2010;Maurice et al 2011Maurice et al , 2012.…”
Section: Turbidity As Tracermentioning
confidence: 99%
“…A short flow distance or travel time between drilling impact and sampling point is a likely prerequisite. However, in the setting of the construction project, tracers typically used in karsts appear to be unfeasible (Goldscheider et al 2008) and other methods approved in boreholes are unpromising (Kogovšek & Petrič 2010;Maurice et al 2011Maurice et al , 2012.…”
Section: Turbidity As Tracermentioning
confidence: 99%
“…Several studies have already shown the problematic of communal landfills in karst areas of Slovenia, which greatly contribute to contamination of karst waters (e.g. Kogovšek & Petrič 2007, 2010. Beside communal landfills, illegal waste disposal is problematic in karst areas, due to their vulnerability and low self-purification processes (Ford & Williams 2007).…”
Section: Problematika Onesnaženosti Jam V Beli Krajinimentioning
confidence: 99%
“…In a case study of the municipal landfill site near Mozelj in southeastern Slovenia (Kogovšek and Petrič 2010a), the functioning of three monitoring boreholes at the margins of the landfill was tested by a combination tracer test. The findings about the characteristics of tracer transport in the karst system and the outflow through karst springs were additionally used to identify the most suitable springs for monitoring and preparing an appropriate sampling regime.…”
Section: Studies Of Karst Aquifers and Their Protectionmentioning
confidence: 99%